Mitral valve prolapse in patients with atrial septal defect: A quantitative three‐dimensional echocardiographic analysis. Issue 6 (23rd May 2022) - Ortiz‐Leon, Xochitl A.; Fritche‐Salazar, Juan F.; Posada‐Martinez, Edith L.; Rodriguez‐Zanella, Hugo; Venegas‐Roman, Alejandra G.; Ruiz Esparza‐Dueñas, Maria E.; Sugeng, Lissa; Arias‐Godinez, Jose A.
Abstract: Introduction and objectives: Mitral valve (MV) prolapse is highly prevalent in patients with atrial septal defect (ASD). Abnormal left ventricular geometry has been proposed as the main mechanism of MV prolapse in ASD, however, the changes in the morphology of the MV apparatus remain to be clarified. Our aim was to assess the MV geometry in patients with ASD and MV prolapse. Methods: We evaluated 99 patients (73% female, median age 40 years) with ASD who underwent a three‐dimensional transesophageal echocardiogram. Three‐dimensional analysis of the MV was done using dedicated automated software. Transthoracic echocardiographic parameters were assessed post ASD closure in 28 patients. Results: MV prolapse was found in 39% of patients. Although smaller left ventricular dimensions and greater interatrial shunt were found in patients with MV prolapse compared with those without prolapse, there was no difference in the subvalvular parameters. MV prolapse was associated with larger mitral anterior‐posterior diameter, anterolateral‐posteromedial diameter, anterior perimeter, posterior perimeter, total perimeter, and anterior leaflet area (all p  < 0.05). Mitral regurgitation was more frequent in patients with MV prolapse (80 vs. 48%, p  = 0.002). Conclusions: In patients with ASD, the main mechanism of MV prolapse is the presence of an organic primary process of the MV apparatus (excessive anterior mitral leaflet tissue and mitral annular enlargement).